Elevation of circulating neutrophil extracellular traps in endometrial cancer: Poor prognostic value of cell-free double-stranded DNA - Yeonju Seo; Se Ik Kim; Sang Hoon Song; Jisoo G. Kim; Ja-Yoon Gu; Hye Won Jeon; Maria Lee; Hyun Kyung Kim (Translational Oncology, 2024)
Objective: Neutrophils produce neutrophil extracellular traps (NETs) by releasing nuclear contents into the extracellular environment. NETs are associated with systemic inflammation and cancer development and progression. We aimed to investigate whether NET markers are associated with the prognosis of endometrial cancer. Methods: Circulating levels of three NET markers (histone-DNA complex, cell-free double-stranded DNA (dsDNA), and neutrophil elastase) were measured in 98 patients with endometrial cancer who underwent surgery as primary treatment between January 2015 and June 2018 and 45 healthy women. Area under the receiver operating characteristic curve (AUC) analyses were conducted to investigate the diagnostic and prognostic utility of the markers for endometrial cancer. Results: Patients with endometrial cancer showed significantly higher levels of the three NET markers than those in healthy controls. In discriminating endometrial cancer patients from healthy controls, the three NET markers showed AUC values in the following order: cell-free dsDNA (0.832; 95 % CI, 0.760–0.889), histone-DNA complex (0.740; 95 % CI, 0.660–0.809), and neutrophil elastase (0.689; 95 % CI, 0.607–0.764), comparable to those of CA-125 (0.741; 95 % CI, 0.659–0.813). Multivariate analysis adjusting for FIGO stage, histology, and lymphovascular space invasion, and lymph node involvement revealed that cell-free dsDNA level (cutoff: 95.2 ng/mL) was an independent prognostic marker for poor progression-free (adjusted HR, 2.75; 95 % CI, 1.096.92; P = 0.032) and overall survival (adjusted HR, 11.51; 95 % CI, 2.0664.22; P = 0.005) for patients with endometrial cancer. Conclusion: High levels of circulating NET markers were observed in patients with endometrial cancer. Cell-free dsDNA levels may play a role as prognostic markers for endometrial cancer.